Table of Content - -, (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content:1. The Beginnings and Endings of Hejaziyat Al-Sharif Al-RadiDr. Khalid Hamid Mohammed Nuwaiher Alghanmi2. Narrative temporal paradoxes in the "Shefrat Bilal" novel - an Applied studyLaila Ahmed Abu Ajami, Etimad Ibrahim Hassan Al-Assad3. The Semiotics of Titling in Very Short Poems: A Study of Contemporary Gulf Poetry Models.Musaad Kareem Jaber Aldhafeeri4. The verbal act in the heritage text "the text of Ismail bin Abi Al-Jahm and Hisham bin Abdul Malik as a model" - a pragmatic studyDr. Rashid Hamoud Al-Farraj5. 5. The dialectic of literary aesthetics between the old and the new: The theory of deviation as a modelDr. Jihad Faiz Al-Islam
Keywords: Journal of Arabic Language and Literature